Paternal sepsis induces alterations of the sperm methylome and dampens offspring immune responses: an animal study - Glosse, Katharina; Schenz, Judith; Uhle, Sandra; Schaack, Dominik; Weigand, Markus A.; Uhle, Florian (Clinical epigenetics, 2018)
Sepsis represents the utmost severe consequence of infection, involving a dysregulated and self-damaging immune response of the host. While different environmental exposures like chronic stress or malnutrition have been well described to reprogram the germline and subsequently offspring attributes, the intergenerational impact of sepsis as a tremendous immunological stressor has not been examined yet.
Gesehen am 20.07.2018